Scientific Investigation of Borreria hispida (Linn) – A Tamil Traditional Medicinal Plant against Hyperlipidemia Disease - C. D. Shaji Selvin; Jambula Dinesh Babu; A. Kottai Muthu (Challenges and Advances in Chemical Science Vol. 3, 2021)
The objective of the present investigation was to evaluate the lipid lowering effect of various extract of whole plant of Borreria hispida (Linn) in high fat fed rats. The whole plant Borreria hispida (Linn) dry powder was extracted with various solvents (PE, EA and methanol) through Soxhlet extracter and crude various extract utilized for hypolipidemic activities. The acute toxicity study was found that all the extracts are safe up to 2000mg/kg, so one tenth of this dose was consider as evaluation dose. Different extracts (Petroleum ether, Ethyl acetate and Methanol) of Borreria hispida (Linn) were administered in dose of 200mg/kg/day to rats fed with high fat diet to assess its possible lipid-lowering potential A total number of 36 animals were divided into 6 groups of six each. Group I normal, Group II High Fat Diet, Group III- High fat diet plus Pet.ether extract (200mg/kg b.wt), Group IV High fat diet plus Ethyl acetate extract (200 mg/kg b.wt), Group V High fat diet plus Methanol extract (200 mg/kg b.wt), Group VI High fat diet plus standard drug atorvastatin (1.2 mg/kg b.wt). There was a noticed increase in the body weight in HFD fed group (p<0.001), which was reduced by the administration of methanolic extract of Borreria hispida (200 mg/kg). The elevated levels of total cholesterol, triglycerides, phospholipids, LDL-C and VLDL-C were observed in rats fed with high fat diet (group II). After treatment of methanolic extract of Borreria hispida (200mg/kg/day) showed a significant (p<0.001) decrement in body weight, plasma and tissue total cholesterol, triglycerides, phospholipids, plasma LDL-C and VLDL-C along with an increase in plasma HDL-C when compared to HFD rats (group II). The similar result was not found in other two extract treatment groups. The methanolic extract of Borreria hispida could protect against atherosclerosis and decrease the atherogenic index than that of other extract treatment groups.This finding provides some biochemical basis for the use of methanolic extract of whole plant of Borreria hispida could protect against atherosclerosis and decrease the atherogenic index, thereby supporting the local use of Borreria hispida in the management of atherosclerosis.